CD36 maintains the gastric mucosa and associates with gastric disease - Jacome-Sosa, Miriam; Miao, Zhi-Feng; Peche, Vivek S; Morris, Edward F; Narendran, Ramkumar; Pietka, Kathryn M; Samovski, Dmitri; Lo, Hei-Yong G; Pietka, Terri; Varro, Andrea; Love-Gregory, Latisha; Goldenring, James R; et al. (Communications biology, 2021)
The gastric epithelium is often exposed to injurious elements and failure of appropriate healing predisposes to ulcers, hemorrhage, and ultimately cancer. We examined the gastric function of CD36, a protein linked to disease and homeostasis. We used the tamoxifen model of gastric injury in mice null for Cd36 (Cd36-/-), with Cd36 deletion in parietal cells (PC-Cd36-/-) or in endothelial cells (EC-Cd36-/-). CD36 expresses on corpus ECs, on PC basolateral membranes, and in gastrin and ghrelin cells. Stomachs of Cd36-/- mice have altered gland organization and secretion, more fibronectin, and inflammation. Tissue respiration and mitochondrial efficiency are reduced. Phospholipids increased and triglycerides decreased. Mucosal repair after injury is impaired in Cd36-/- and EC-Cd36-/-, not in PC-Cd36-/- mice, and is due to defect of progenitor differentiation to PCs, not of progenitor proliferation or mature PC dysfunction. Relevance to humans is explored in the Vanderbilt BioVu using PrediXcan that links genetically-determined gene expression to clinical phenotypes, which associates low CD36 mRNA with gastritis, gastric ulcer, and gastro-intestinal hemorrhage. A CD36 variant predicted to disrupt an enhancer site associates (p < 10-17) to death from gastro-intestinal hemorrhage in the UK Biobank. The findings support role of CD36 in gastric tissue repair, and its deletion associated with chronic diseases that can predispose to malignancy.
Keywords: Gastrointestinal Hemorrhage; žaludeční sliznice; Male; Endothelial Cells; endoteliální buňky; mužské pohlaví; gastrointestinální krvácení; CD36 Antigens; žaludeční vředy; Gastritis; gastritida; Animals; ženské pohlaví; zvířata; antigeny CD36; myši inbrední C57BL; myši; Mice, Inbred C57BL; Stomach Ulcer; Mice; Female; Gastric Mucosa